Analysis Policy Overtime And Culture Organization To Employee Performance Bank Syariah Indonesia (BSI) PALOPO Branch Office - Muh. Hidayat Yasruddin; Saharuddin; Sari Ratna Dewi (LP2M IAIN Palopo, 2025)
writing of this research article entitled